THEORETICAL FOUNDATIONS OF MILITARY PSYCHOLOGY AND PEDAGOGY - Murodov Akmal Djayliboevich. (Scholar Express Journal, 2022)
One of the most significant moments in a person's life is when they decide whether to become a military man, a protector of their country, or enlist for conscription. A young (teen) person who is summoned to serve in the military for a set period of time, who is enrolled in a higher military institution, or who expresses a willingness to undertake military service on a contractual basis is required, first and foremost, to give up his usual way of life and walk. Because of the demands of universal laws, rigid subordination, and military discipline, life and activities in military groups, communities, are regulated. Opinions and observations on the theoretical underpinnings of military psychology and pedagogy are maintained in this article
Keywords: Military Man; Pedagogy; Theory; Military Charter